2021
DOI: 10.1007/s00167-021-06657-x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation exercise therapy improves pain, muscle strength, and kinesiophobia following total knee arthroplasty in the short term: a randomized controlled trial

Abstract: Purpose This study aimed to compare progressive muscle relaxation (PMR) + standard physiotherapy (PT) to standard PT during inpatient rehabilitation of total knee arthroplasty (TKA) patients in terms of post-operative outcomes. The hypothesis was that PMR + standard PT would lead to better pain, function, and neuromuscular outcomes than standard PT. Methods A total of 106 patients were randomly allocated into PMR or standard rehabilitation (SR) groups. Both groups received standard PT during their hospital sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Positive effects of mind–body interventions, and especially mindfulness meditations are widely reported for a range of diseases ( Sampaio et al, 2017 ). While the effect of such an adjunct therapy approach has still to be evidenced in FRI patients ( Walter et al, 2022a ), improvements in functional outcomes were reported in patients undergoing primary arthroplasty procedures after relaxation exercise ( Lim et al, 2014 ; Eymir et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Positive effects of mind–body interventions, and especially mindfulness meditations are widely reported for a range of diseases ( Sampaio et al, 2017 ). While the effect of such an adjunct therapy approach has still to be evidenced in FRI patients ( Walter et al, 2022a ), improvements in functional outcomes were reported in patients undergoing primary arthroplasty procedures after relaxation exercise ( Lim et al, 2014 ; Eymir et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, patients with a decreased PPT received signal inputs by stimulations that would be barely noticeable under normal conditions, and a mechanism that restricts movement was activated at the level above the spine, leading to decreased motor functions. Another possible explanation for the relationship between pain and the motor system is that pain reduction may lead to decreased motor phobia, resulting in an increased ROM [11]. Therefore, it is important to control pain preoperatively and postoperatively, and appropriate postoperative analgesics should be provided to prevent any prolonged decrease in pain thresholds and to achieve favorable postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests psychosocial factors such as kinesiophobia (fear of movement/reinjury), preoperative mental health and pain catastrophizing may influence return to sport [9,10]. While kinesiophobia has been predominantly recognized as affecting outcomes following anterior cruciate ligament reconstruction (ACLR) [11][12][13], shoulder arthroscopy [14][15][16], hip [17] and total knee arthroplasty (TKA) [18,19], there is still limited evidence describing it's effects on RTS and clinical outcomes after OCA transplantation of the knee [20].…”
Section: Introductionmentioning
confidence: 99%